Analysis of the Implementation of Chemistry Learning Assisted by Interactive Media AI Chatbot Based on ChatGPT as Teaching Tool for Students - Yunitasari, Yunitasari; Putra, Syalendra; Firdaus, Lutfi; Widi Winarni, Endang (Corolla International Conference, 2024)
The objective of this research are to describe how do students in the Fatmawati Sukarno State Islamic University Science Education Study Program react to interactive AI chatbot media based on ChatGPT as a learning aid in the study of basic chemistry, and how well do students in the Science Education Study Program at Fatmawati Sukarno State Islamic University comprehend the concept after using interactive AI Chatbot media based on ChatGPT as a learning aid in simple chemistry learning. This kind of study uses a qualitative descriptive methodology. Researchers use observation, questionnaires, interviews, and documents to gather data. According to the study’s findings, students’ answers to interactive AI chatbot media based on ChatGPT as a learning aid yielded an average percentage with an interpretation interval value of "Very Good" for the ChatGPT-based AI chatbot media learning method. Following their use of AI CHATGPT media, pupils demonstrated a deeper comprehension of fundamental chemical principles. The use of ChatGPT-based AI chatbot media as a teaching tool has been shown to improve student engagement.